Model Pemilihan Moda Dengan Metode Ahp (Analytical Hierarchy Process) (Studi Kasus: Perumnas Palur, Desa Ngringo, Kecamatan Jaten, Kabupaten Karanganyar) - Hardiyanti, Annisaa Putri; , Nurul Hidayati, ST., MT., Ph.D (2016)
The needs of transportation is increasing from year to year, it is influenced by the development of an area such as Perumnas Palur located in the Village Ngringo, District Jaten of Karanganyar. The layout is exactly located in a strategic area with many public facilities. This has effect in society activities that influenced the modal choice. Activity modal choice in Perumnas Palur aims to investigate the trip characteristics, socioeconomic characteristics, and modeling of Analytical Hierarchy Process (AHP), also the criteria of modal choices reason. The data is carried out from trip and socioeconomic characteristics questionnaires, also criteria of modal choice questionnaire, all of that filled by citizens. The trip characteristics of the society dominantly using the motorcycle for working, many trips taken more than 5 times of week within the time less than 15 minutes and costs less than Rp10,000.00. While the results of the socioeconomic characteristics represent that mostly consists of housewives and private employees with average income Rp1.714.103,00. The AHP results fairly appropriate to the circumstances in Perumnas Palur in general, with the models of AHP is Pm = Xm1.Y1 + Xm2.Y2 + Xm3.Y3 + Xm4.Y4. With the rank of the modal choice based on the reasons of criteria, i.e. motorcycle (27.5%), walking (26.6%), car (18.5%), bike (15%), and bus (12.4%) from the criteria of the reasons safe (47.5%), time (24%), easy (17%), and fees (11.5%).